Can learning beyond the classroom impact on social responsibility and academic attainment? An evaluation of the Children's University youth social action programme. (June 2019) - Siddiqui, Nadia; Gorard, Stephen; See, Beng Huat
Highlights: Participation in out-of-school social action can improve pupils' primary school attainment. A small improvement in the non-cognitive outcomes of 'teamwork' and 'social responsibility'. It is only fair that wider opportunities at school are made easier for disadvantaged pupils. Abstract: Disadvantaged pupils in England tend to have lower average attainment than their peers. They are also less likely to be involved in wider learning and opportunities for experience beyond the classroom walls. Approaches which support learning activities beyond the traditional classroom might assist in overcoming the persistent achievement gap of disadvantaged pupils, as well being valuable in their own right. This paper presents impact evidence of a school programme called Children's University (CU) for pupils in primary schools which combines outdoor learning activities, after-school clubs and community social action. The evaluation funded involved 1840 year 5 pupils in 68 primary schools, randomised into treatment and waiting-list control (business-as-usual) groups. The programme was delivered for two consecutive years after which the academic and non-cognitive outcomes were re-assessed. The findings suggest that after two years of opportunity to participate in out-of-school hour activities and social action there is a link to slight progress in pupils' reading and maths performance ('effect' sizes of 0.12 and 0.15). A smaller improvement in non-cognitive outcomes of 'teamwork' and 'social responsibility' was also found ('effect' sizes of 0.02 and 0.07). The gains in teamwork and social responsibility results for disadvantaged pupils eligible for free school meals (FSM) were better than the overall figures, suggesting that this intervention may have a role to play in reducing the poverty gradient in such social 'skills'. It is only fair that wider opportunities at school are made easier for disadvantaged pupils, they may have others benefits. However, if changes in attainment alone are the primary goal, these relatively small effect sizes suggest that there will be more cost-effective routes than the one described in this paper.